Violência autoinfligida em Betim: tentativas de suicídio e fatores associados - Ana Maria Barros Peres (2017)
The current scenario of Public health is facing, in Brasil and in world, the phenomenon that challenges it: violence. Suicide is one of the forms of violence and, in the world, there are more deaths from suicide than from war and homicide. In recent years, suicide has increased significantly in low-and middle-income countries, and most countries do not have a prevention strategy. When studing the morbidity and mortality profile of sel-inflicted violence, specifically, suicide attempts, in Betim-MG. For this, the psychosocial approach was carried out, dialoguing with different theoretical formulations: Émile Durkheim, Sigmund Freud and Neury José Botega. As a methodology, the cross-sectional survey of the health and violence (SAUVI) survey was conducted in 2014 and 2015 by the Postgraduate Program on health promotion and prevention of violence, in the municipality of Betim-MG. The dependent variables: suicide attempts by the interviewee; attempted suicide by someone in the household; half used and reason. The explanatory variables: socio-demographic (sex, age, schooling, marital status, color, income, occupation); culture (religion, types of participation in groups, types of violence); diseases (cancer, depression, anxiety/other psychiatric problem); drugs, sleeping pills and alcohol intake; family income and other types of violence. Made descriptive analyzes, with frequency distribution, bivariate and multivariate, namely, logistic regression model and correspondence analysis. In the results showed the association of suicide attempts by the interviewee (p<0,05) with: sex, income, occupation, participation in self-help groups (alcoholics anonymous), lack of access to social law; different types of violence , emotional/mental disorders and use of sleeping pills. The association of suicide attempts by relatives with low family income and other types of violence was verified; the final logistic regression model showed association with the variables sex, taking sleeping pills and non participation in groups such as NGOs, religious groups, among others; the correspondence analysis showed a greater association of those interviewed who attempted suicide due to sadness/depression with females with history of suicide in the family. Attempts of suicide by: financial crisis had an association with the female sex, without history of suicide in the family and with the male sex, with suicide record in the family; already the attempts of suicide of the interviewed due to family crisis had greater association with the male sex without record of suicide in the family , and the same occurring greater association when using cutting object/firearm; poisoning/intoxication/others, was associated to the female independent of the family history; male interviewees and with record of suicide in the family showed more associated with suicide attempts by hanging/jumping from high place. It is conclude that suicide attempts are associated with several factors, which opens possibilities for its approach and prevention.